Chapter Gli studi letterari cognitivi e lo statuto dell'interpretazione: un tentativo di mappatura teorica - Caracciolo, Marco (Moderna/Comparata, 2022)
What is the role of interpretation-the close reading of individual texts-in cognitive literary studies? In attempting to come to grips with this vexed question, my article focuses on the complex divides that separate the practice of interpretation from cognitive-scientific research. I argue that cognitive literary studies can only fulfill their potential by moving beyond interpretation, and I survey lines of research that have already put into practice this intuition. Secondly, I explore a heuristic use of interpretation, where insights from cognitive science are leveraged-in what I call a "cognitive thematics"-to illuminate a background of metacognitive questions.